Russia : Bank Assistance for Social Protection - Thompson, Lawrence H. (World Bank, Washington, DC, 2016)
This paper is one of the background papers prepared as an input to the Russia Country Assistance Evaluation (CAE) by the Operations Evaluation Department (OED) of the World Bank. In 1992, the Russian Federation commenced reforms to transition to a market economy. This report focuses on the following projects: the Employment Services and Social Protection Loan (ESSP), the Social Protection Adjustment Loan (SPAL), and the Social Protection Implementation Loan (SPIL). From the beginning of its relationship with Russia, the Bank viewed social protection reform as one of the most important elements of its country assistance strategy, largely out of concern that a breakdown in the social safety net would undermine political support for economic reform. In general, the outcome of social protection efforts during the first part of the 1990s was moderately satisfactory and the outcome in the second half of the decade was moderately unsatisfactory. The ESSP was created to ensure a proper response to an anticipated rise in unemployment claims as a result of industrial restructuring and later changed to focus mostly on computerisation and upgrading the data processing capacity of local social protection offices dealing with pension payments. The SPAL-SPIL package addressed most of the important remaining social protection reforms, but with mixed success. Major barriers to success were the poor fiscal conditions prevailing through most of the 1990s, and the unsatisfactory performance of both the Bank and the borrower during the latter half of the 1990s. Lessons to be learned from the Bank’s experience in Russia in the 1990s include the need to: (a) pay more attention to the political and institutional aspects of the reform process; (b) have reasonable expectations about the pace at which reforms can be developed, adopted, and implemented (c) deal with all of the relevant units of government, and not just the federal executive; and (d) employ lending vehicles with more flexibility to adjust lending activities as the policy development and implementation process passes through its various phases. Overall, the author has presented a thorough, professional analysis covering all major aspects of co-operation between the Russian Federation and the Bank in the social protection area in the 1990s.